Early Surgical Stabilization of Complex Chest Wall Injuries Improves Short-Term Patient Outcomes. (1st August 2018) - Iqbal, Hafiz J.; Alsousou, Joseph; Shah, Sohan; Jayatilaka, Lara; Scott, Sharon; Scott, Simon; Melling, David
Abstract : Background: This study aimed to assess the outcome of patients undergoing internal fixation of complex rib fractures in a U.K. major trauma center. Methods: A retrospective analysis was performed on all patients undergoing operative fixation of rib fractures from March 2014 to May 2016. Outcome measures included hospital length of stay, intensive care unit (ICU) admission, mechanical ventilation, infection, and mortality. Results: One hundred and two patients (66 male patients and 36 female patients, with a median age of 62 years) underwent rib fracture fixation during the study period. The causes of trauma were road traffic accidents in 39 patients (38%), a fall from a substantial height in 38 patients (37%), and a fall down stairs in 21 patients (21%). Thirty-eight patients (37%) had isolated chest trauma, and 64 patients (63%) had additional injuries. Fifty-three patients (52%) required ICU admission with a mean ICU stay of 4.7 days (range, 1 to 34 days). The median hospital length of stay was 10.6 days (range, 3 to 51 days). Patients with additional injuries (p = 0.01) and those requiring mechanical ventilation (p < 0.0001) stayed significantly longer. Sixty-five patients (64%) underwent rib fixation within 48 hours of the injury, and 37 patients (36%) underwent the surgical procedure after 48 hours. A surgical procedure within 48 hours resulted in a shorter ICU stay (p = 0.01), fewer cases of pneumonia (p = 0.001), reduced duration of mechanical ventilation (p = 0.03) and fewer tracheostomies (p = 0.02), and shorter hospital length of stay (11.5 compared with 17.3 days; p = 0.008). Conclusions: Surgical stabilization of multiple rib fractures may improve the outcome in patients with multiple injuries and isolated chest wall trauma. Early surgical fixation leads to shorter length of stay and better outcomes. Level of Evidence: TherapeuticLevel III . See Instructions for Authors for a complete description of levels of evidence.